Strategi Konten Storytelling pada Akun Instagram @bolacomid Dalam Pemenuhan Informasi Penggemar Sepak Bola - Salsabilla, Aldika Tiara; Putra Bhakti, Aditya Dwi (MEDIASI Jurnal Kajian dan Terapan Media, Bahasa, Komunikasi, 2026)
The dissemination of sports information requires speed, interactivity, and visual appeal. This study analyzes the Instagram management strategy of @bolacomid as an information medium for fanatic football fans. Using the Circular of SOME theory by Regina Luttrell and Textual Poachers theory by Henry Jenkins, this research applies a qualitative descriptive case study approach. Data were collected through interviews with the social media leader and admin, and direct observation of account activities. The results show that @bolacomid’s strategy includes the Share, Optimize, Manage, and Engage stages, focusing on Engage to create audience participation. Moreover, @bolacomid acts as an active audience practicing Textual Poaching by reinterpreting football fandom culture. This proves that effective Instagram management focuses not only on delivering information but also on building emotional connections and account engagement.